A Critical Review of Russia’s Energy Efficiency Policies in the Construction and Housing Sector - Alekseev, Alexander N.; Lobova, Svetlana V.; Bogoviz, Aleksei V.; Ragulina, Yulia V. (International Journal of Energy Economics and Policy, 2019)
The paper critically reviews the existing energy efficiency policies in the construction and housing sector of Russia, focusing on the following: (i) the government management system; (ii) technological regulations; (iii) financial incentives and funding; (iv) and supporting mechanisms. The methodology used by the Government of Russia to specifically monitor energy efficiency performance in the construction and housing sector is evaluated, with the use of statistical data obtained from the government statistical service. On the basis of the conducted review, the paper proposes three recommendations for the Government of Russia, which could become the first step for improving energy efficiency policies in the construction and housing sector: (i) to provide an appropriate assessment of the energy efficiency potential; (ii) to develop a comprehensive regulatory framework and implementation mechanisms aimed at increasing energy efficiency; (iii) to develop a clear causal mechanism between energy efficiency policies and actual performance, which could be quantitatively measured using an appropriate methodology. Keywords: Energy Efficiency, Construction and Housing, Russia JEL Classifications: Q43, Q48, L74, L78, N64 DOI: https://doi.org/10.32479/ijeep.7608